The effects of sarcopenia on the complications after esophagectomy with simultaneous plasty of the esophagus - Natalia B. Kovalerova; Dmitry V. Ruchkin; Oleg V. Strunin; Diana E. Okonskaya; Alina V. Mazurok (Клиническая практика)
BACKGROUND: Large meta-analyses have proven the negative effects of sarcopenia on the rates of postoperative complications and mortality, on the duration of the postoperative stay at the In-Patient Department and on the 1-, 3- and 5-year survival of the patients. However, given that in coloproctology and emergency surgery, the effects of sarcopenia on the outcomes are undoubtful, in the esophageal surgery the results are extremely controversial. AIM: to evaluate the effects of sarcopenia on the complications in patients after esophagectomy with simultaneous esophageal plasty. Methods: At the National Medical Research Center of Surgery named after A.V. Vishnevsky (NMRCS), a retrospective computed-tomographic diagnostics of sarcopenia was carried out among the patients (n=111) before undergoing esophagectomy with simultaneous esophageal plasty due to the presence of benign or malignant diseases of the esophagus. The perioperative management of all the patients was carried out within the framework of the programs of rationally accelerated perioperative rehabilitation. For the purpose of quantitative evaluation of sarcopenia, the musculoskeletal index was measured. Using the logistic regression, we have evaluated the effects of preoperational sarcopenia on the postoperative complications. RESULTS: Sarcopenia of various degree of intensity was diagnosed in 95 (85.6%) patients. The analysis of the adjusted odds ratios did not reveal any statistically significant relation between sarcopenia and postoperative complications. CONCLUSION: The experience gained at the NMRCS has shown that high-quality surgical technique together with competent perioperative management are able to alleviate the negative effects of sarcopenia on the postoperative complications.